2022
DOI: 10.1007/s12310-022-09501-w
|View full text |Cite
|
Sign up to set email alerts
|

A School-Based Approach to Building Resilience and Mental Health Among Adolescents on the Autism Spectrum: A Longitudinal Mixed Methods Study

Abstract: Tackling mental health difficulties in adolescents on the autism spectrum requires a comprehensive prevention approach. A 3-year multisite proof-of-concept longitudinal study implemented an evidence-based multilevel resilience intervention in schools to promote protective factors at the adolescent, parent, and school level. The intervention, consisting of the adolescent, parent and teacher components of the Resourceful Adolescent Program–Autism Spectrum Disorder (RAP-ASD) augmented with the Index for Inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Although some of these may already incorporate elements of coping and resilience among their areas of focus (McGillivray & Evert, 2014 ; Oswald et al, 2018 ), interventions with an explicit focus on stress reduction and management in autistic adults are relatively limited. Further, while there are promising programs referred to as resilience interventions with autistic youth (e.g., Resourceful Adolescent Program–Autism Spectrum Disorder, RAP‐ASD; Shochet et al, 2022 or Resilience Builder Therapy Program, RBP; Habayeb et al, 2017 ), these interventions do not incorporate resilience as a primary target or outcome measure. As far as we know, stress interventions are yet to be designed and conducted in autistic adults, which specifically target and measure coping strategy use and resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Although some of these may already incorporate elements of coping and resilience among their areas of focus (McGillivray & Evert, 2014 ; Oswald et al, 2018 ), interventions with an explicit focus on stress reduction and management in autistic adults are relatively limited. Further, while there are promising programs referred to as resilience interventions with autistic youth (e.g., Resourceful Adolescent Program–Autism Spectrum Disorder, RAP‐ASD; Shochet et al, 2022 or Resilience Builder Therapy Program, RBP; Habayeb et al, 2017 ), these interventions do not incorporate resilience as a primary target or outcome measure. As far as we know, stress interventions are yet to be designed and conducted in autistic adults, which specifically target and measure coping strategy use and resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Common limitations in the quantitative studies include inappropriate sample size and lack of detailed report on analytic methods. Only two out of the seven intervention studies reported on statistical significance [47,49]. Common limitations in the qualitative studies include limited description of data analysis, limited verification procedure to establish credibility and no reflexivity of the account.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…Participants in the seven intervention studies included autistic students (n = 102, male n = 82, female n = 20) ranging from 8 years old to 17 years old (mean = 13.34), and one study did not report age ranges, only grade levels (grades six to eight) [41]. Three studies included only male students [42,44,46], and four studies contained both male and female students [41,45,47,49]. Among the six studies investigating the different perspectives and experiences, three studies examined the views of autistic students and youth (n = 72) [10,48,51], with one study including the views of parents (n = 18) on the types of strengths autistic students have [51], and three studies investigated the experiences and perspectives of school staff (n = 123), including teachers, principals, education support officers and administrative assistants [40,43,50].…”
Section: Participant Groups Identified Within the Studiesmentioning
confidence: 99%
See 2 more Smart Citations